JAMES JUNKER: POST-COLD WAR HORIZONS OF THE WORLD STATE - Gajic, Aleksandar (Political Review, 2024)
Starting from the circumstances in the post-Cold War period, the Paper provides a cross-section through theoretical works that are trying to revive interest in the idea of global supranational integration, ie the idea of the World State, regardless of whether they treat it affirmatively, ambivalently or negatively. Then, among the rare examples of affirmative attitude towards the realization of the idea of the World State, the work is focused on the proposal of the American economist James Junker presented in his books “World Union on the Horizon” (1993) and “The Idea of World Government: From Ancient Times to the 21st Century” (2011). The Paper, using analytical and synthetical methods, analyzes in detail Junker's economic views and institutional proposals for building a “minimal” World State (which he calls the Federal Union of Democracies) as well as his global plan to bridge the gap between the rich North and the poor South, which he sees as main obstacle of supranational integration. The final part of the Paper gives a critical review of Junker's ideas, which takes into account modern economic and political processes at the time of the emergence of a multipolar world. The growth of a multipolar world on the remains of its bipolar and unipolar predecessors shows other economic tendencies than those predicted by Junker. The new regional centers of power are interconnected and have their own interregional initiatives based on mutual benefit, beyond the West and its plans to reduce the economic gap between North and South. Now poor South isn`t waiting for help from the developed North (i.e., the West), but it is getting the basis for independent development from the East, ie. its strengthening centers of power. All in all, although evidently flawed, one-sided, and naive, Junker's moderate proposal for a Federal Union of global reach stands as one of the few original proposals for a “minimum” World State in the post-Cold War era. With all his atypicality, Junker’s proposal maintains the hope of the proponents of the idea of the World state who are still convinced that the risks of embarking on such ventures are not only justified but also necessary, taking into account the potential advantages of global political integrations both in the field of economy, politics, social sphere and ecology.
Keywords: World state; supranational integrations; James Juncker; post-Cold War world; global economy